A Lifetime of Difference - Devine, Nesta (Indiana University Press, 2024)
In this memoir I track the people, events and influences which have had a bearing on my ability to work alongside Māori and Pacific students and academics. From a childhood in rural Aotearoa New Zealand, through sporadic and prolonged university studies, to teaching in Schools of Education at the University of Waikato and Auckland University of Technology, I have always been fascinated by the possibilities of thinking differently. This underpins my experience in supervising and supporting Māori and Pasifika academics, at the post graduate level and as early career researchers.